SIMPLE EQUATION FOR WALL-COLUMN CONTACT LENGTH TO ESTIMATE THE LATERAL STRENGTH OF REINFORCED CONCRETE FRAMES WITH MASONRY INFILL WALLS - Abdurrasyid, Yunus; Maidiawati,; Tanjung, Jafril; Ridwan, Muhammad (Journal of Applied Engineering Science, 2026)
This work introduces an analytical approach for assessing the seismic capacity of brick masonry infills within reinforced concrete frame structures by the use of a diagonal strut model. The model demonstrates that when the column experiences flexural displacement and the masonry wall endures shear deformation, separation or contact transpires between the masonry infill and the column. The contact height between the masonry infill and column was determined based on the compatibility of lateral displacements of both elements. As a result, a simple equation of contact length between infill and column to determine the lateral strength of masonry infill was employed to calculate the strut width of the masonry infill. The lateral strength for several reinforced concrete frame structures with brick masonry infills was determined using the simplified contact length equation. Furthermore, the analytical results were validated using lateral strength of structure models as outcomes of the pushover method. The results showed that the lateral forces of the structures were relatively similar between the analytical and pushover methods. It suggests that the strut model and the simplified wall-column contact height can be used to estimate the lateral strength of masonry infill in reinforced concrete structures.
Keywords: analytical strut model, infill-column contact length, lateral strength, masonry infill, reinforced concrete frames